Large scale atomistic simulation with electrostatics: The case of cation impurity segregation along an edge dislocation line - Zhang, F.; Wright, Kathleen; Gale, Julian; Walker, A. (2010)
The movement of impurities and point defects in materials plays a key role in determining their rheological properties, both by permitting diffusional creep and by allowing recovery by dislocation climb. Impurity and point defect diffusion can also control the kinetics of phase transitions and grain growth, and can determine the rate of chemical equilibration between phases. Thus the study of point defects and their migration has been of considerable interest. So far, studies using computer simulation methods have concentrated on point defects moving through otherwise perfect crystals. Here, we report calculations on the behavior of the isovalent substitutional cation impurities, Ca and Sr, close to the core of an 1/2<110>{11¯0} edge dislocation in MgO. By mapping the distribution of energies for impurities and point defects around the dislocation line, we reveal that the impurities are segregated towards and trapped inside the MgO edge dislocation core. In addition, Mg vacancies will strongly partition to the impurity bearing dislocation. We also find that the presence of impurities slightly increases the Mg migration activation energy. However, impurity migration in the dislocation core is substantially enhanced compared to migration through the dislocation-free crystal structure. Activation energies are 0.76-0.86 of the barrier in the perfect crystal, demonstrating the importance of pipe diffusion along extended defects for low temperature mobility in ionic materials. © 2010 IEEE.